2012
DOI: 10.1194/jlr.m022897
|View full text |Cite
|
Sign up to set email alerts
|

AMPK activation with glabridin ameliorates adiposity and lipid dysregulation in obesity

Abstract: Obesity is characterized by excessive accumulation of lipid metabolites in adipose tissues as well as in nonadipose tissues, such as liver, muscle, and pancreas ( 1 ). Because obesity is considered as a major risk factor for most metabolic diseases, including hyperlipidemia, hypercholesterolemia, type 2 diabetes, hypertension, and cardiovascular disease ( 2-4 ), numerous investigations have been conducted to elucidate the key components in energy homeostasis, which is crucial to develop therapeutic agents for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 60 publications
2
53
1
Order By: Relevance
“…Unhealthy lifestyle factor such as smoking [12], alcohol drinking [13,14], sedentary lifestyle [15], overweight and obesity [16,17] are risk factors of hypercholesterolemia. Consistent with other studies, health-related behavioral factors, such as drinking was substantially associated with hypercholesterolemia in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Unhealthy lifestyle factor such as smoking [12], alcohol drinking [13,14], sedentary lifestyle [15], overweight and obesity [16,17] are risk factors of hypercholesterolemia. Consistent with other studies, health-related behavioral factors, such as drinking was substantially associated with hypercholesterolemia in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al have studied the direct effect of Glab on AMPK activity in obese rodents models (C57BL/6J mice)[107]. They observed that Glab decreases adiposity and ameliorates lipid dysregulation as well as insulin resistance, thus, lowering body weight.…”
Section: Reported Biological Activitiesmentioning
confidence: 99%
“…1), an isoflavan, was firstly isolated from the root of Glycyrrhiza glabra Linne in 1976 [13]. It has been extensively studied and has a variety of pharmacological activities, such as prevention of low density lipoprotein oxidation [14], anti-inflammatory properties [15], neuroprotective effects [16], estrogenic properties [17] and regulation of energy expenditure and metabolism [18]. In addition, it also has some less frequently reported biological activities like antimicrobial activity [19], anti-cancer properties [20] and inhibition of melanogenesis [21].…”
Section: Introductionmentioning
confidence: 99%